Phosphor particle, composite, wavelength conversion member and projector
Phosphor particles made of CASN and/or SCASN, manufactured via specific processes, enhance the color gamut of projectors by optimizing blue light transmission and conversion, addressing the inefficiencies of conventional phosphors in wavelength conversion members.
Patent Information
- Application Number
- JP2022540134
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-30
- Filing Date
- 2021-07-09
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2041-07-09
AI Technical Summary
Conventional phosphors used in wavelength conversion members for projectors are not optimized for high luminous efficiency and do not consider the characteristics of light emitted from the opposite side of the blue light source, affecting the projector's performance, particularly the color gamut.
Phosphor particles composed of CASN and/or SCASN, manufactured through specific processes involving mixing, firing, low-temperature firing, pulverization, decantation, and acid treatment, are designed to achieve a ratio of blue light transmission and conversion efficiency that enhances the color gamut of projectors.
The designed phosphor particles improve the color gamut of projectors by ensuring a balanced transmission and conversion of blue light into red light, reducing heat generation and maintaining high luminous efficiency.
Smart Images

Figure 0007606521000002 
Figure 0007606521000003 
Figure 0007606521000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a phosphor particle, a composite, a wavelength conversion member, and a projector. More specifically, the present invention relates to a phosphor particle for manufacturing a wavelength conversion member of a projector, a composite using the particle, a wavelength conversion member including the composite, and a projector including the wavelength conversion member. [Background technology]
[0002] There are several types of projectors capable of projecting color images, and in recent years, a type using a blue laser light has been actively considered. This type of projector usually includes a blue light source and a wavelength conversion member in which a wavelength conversion layer containing a phosphor that converts the blue light from the blue light source into green light or red light is formed on a transparent substrate. Usually, green light or red light can be obtained by passing (transmitting) the blue light through the wavelength conversion member. By the way, the wavelength conversion member rotates when the projector is in use so that blue light is not continuously irradiated on a specific location. Because of this mechanism, the wavelength conversion member in a projector is often called a "phosphor wheel."
[0003] For example, Patent Document 1 describes a wavelength conversion element having a substrate and a phosphor layer provided on the substrate, and a projector equipped with this wavelength conversion element. The volume concentration of the phosphor in the phosphor layer of this wavelength conversion element is 15 vol% or more. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-162021 A Summary of the Invention [Problem to be solved by the invention]
[0005] It goes without saying that it is preferable for the phosphor used in the wavelength conversion member to have high luminous efficiency / light conversion efficiency of the phosphor itself. In addition, for example, if the wavelength conversion member is a transmissive type, the characteristics of the light emitted from the "opposite side" of the blue light source are important in determining the performance of the projector (for example, the width of the color gamut).
[0006] However, according to the findings of the present inventors, conventional phosphors have not been designed with consideration for application to wavelength conversion members of projectors, and there is room for improvement. For example, conventional phosphors (phosphor particles) used in the manufacture of white LEDs are not suitable for the manufacture of wavelength conversion members of projectors.
[0007] The present invention has been made in view of the above circumstances. It is an object of the present invention to provide phosphor particles that can be preferably applied to the manufacture of wavelength conversion members for projectors. [Means for solving the problem]
[0008] The present inventors have completed the invention provided below and have solved the above problems.
[0009] The present invention is as follows.
[0010] A phosphor particle for manufacturing a wavelength conversion member of a projector, which is made of CASN and / or SCASN, Phosphor particles, wherein a cured sheet produced by the following sheet production procedure satisfies the following optical properties: <Sheet manufacturing procedure> (1) 40 parts by mass of the phosphor particles and 60 parts by mass of silicone resin OE-6630 manufactured by Dow Corning Toray Co., Ltd. are mixed and degassed using a rotation-revolution mixer to obtain a uniform mixture. (2) The mixture obtained in (1) is dropped onto a transparent first fluororesin film, and a transparent second fluororesin film is further laminated on the dropped mixture to obtain a sheet-like material. This sheet-like material is formed into an uncured sheet using a roller having a gap of 50 μm larger than the total thickness of the first fluororesin film and the second fluororesin film. (3) The uncured sheet obtained in (2) above is heated at 150° C. for 60 minutes, after which the first fluororesin film and the second fluororesin film are peeled off to obtain a cured sheet having a thickness of 50±5 μm. <Optical properties> When the intensity at the peak wavelength of blue light emitted from a blue LED having a peak wavelength in the range of 450 nm to 460 nm is Ii [W / nm], and when the blue light is irradiated onto one side of the cured sheet, the intensity of the peak wavelength in the range of 450 nm to 460 nm of the light emitted from the other side of the cured sheet is It [W / nm] and the intensity of the peak wavelength in the range of 600 nm to 650 nm is Ip [W / nm], It / Ii is 0.2 or less and Ip / Ii is 0.05 or more.
[0011] The present invention also provides the following.
[0012] A composite comprising the above phosphor particles and a sealant that seals the above phosphor particles.
[0013] The present invention also provides the following.
[0014] A wavelength conversion member comprising the composite.
[0015] The present invention also provides the following.
[0016] A projector comprising the wavelength conversion member. Effect of the Invention
[0017] According to the present invention, phosphor particles that can be preferably applied to the manufacture of wavelength conversion members for projectors are provided. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a diagram illustrating an example of a wavelength conversion member. [Diagram 2] FIG. 1 is a diagram supplementing the evaluation methods in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. The drawings are for illustrative purposes only. The shapes and dimensional ratios of the components in the drawings do not necessarily correspond to the actual products.
[0020] In this specification, unless otherwise specified, the expression "X to Y" in the explanation of a numerical range means from X to Y. For example, "1 to 5% by mass" means "from 1% by mass to 5% by mass".
[0021] In this specification, "LED" is an abbreviation for Light Emitting Diode. In this specification, the term "phosphor particles" may refer to phosphor powder, which is a collection of phosphor particles, depending on the context.
[0022] <Phosphor particles for manufacturing wavelength conversion components for projectors> The phosphor particles of this embodiment are used for manufacturing a wavelength conversion member for a projector. That is, the phosphor particles of this embodiment are used for manufacturing a wavelength conversion member for converting blue laser light into another color (green or red) in a projector equipped with a blue laser. The phosphor particles of this embodiment are made of CASN and / or SCASN, and therefore usually convert blue light into red light. A cured sheet produced using the phosphor particles of this embodiment according to the following sheet production procedure satisfies the following optical properties.
[0023] <Sheet manufacturing procedure> (1) 40 parts by mass of phosphor particles and 60 parts by mass of silicone resin OE-6630 manufactured by Dow Corning Toray Co., Ltd. are mixed and degassed using a rotation-revolution mixer to obtain a uniform mixture. (2) The mixture obtained in (1) above is dropped onto a transparent first fluororesin film, and a transparent second fluororesin film is further laid on top of the dropped mixture to obtain a sheet-like material. This sheet-like material is formed into an uncured sheet using a roller having a gap of 50 μm larger than the total thickness of the first fluororesin film and the second fluororesin film. Here, "forming into an uncured sheet using rollers having a gap" means passing a sheet-like material through the gap between a pair of rollers placed opposite each other. The first fluororesin film and the second fluororesin film are preferably the same film, in which case the roller gap is twice the thickness of one film plus 50 μm. (3) The uncured sheet obtained in (2) above is heated at 150° C. for 60 minutes, after which the first fluororesin film and the second fluororesin film are peeled off to obtain a cured sheet having a thickness of 50±5 μm.
[0024] <Optical properties> When the intensity at the peak wavelength of blue light emitted from a blue LED having a peak wavelength in the range of 450 nm to 460 nm is Ii [W / nm], and when the blue light is irradiated onto one side of the cured sheet, the intensity at the peak wavelength in the range of 450 nm to 460 nm of the light emitted from the other side of the cured sheet is It [W / nm], and the intensity at the peak wavelength in the range of 600 nm to 650 nm is Ip [W / nm], It / Ii is 0.2 or less, and Ip / Ii is 0.05 or more.
[0025] The inventors considered that, in order to obtain phosphor particles suitable for manufacturing wavelength conversion components for projectors, the phosphor particles should be designed taking into consideration the wavelength conversion mechanism in projectors, i.e., how blue light "passes through (transmits)" the wavelength conversion component to obtain green light or red light. Based on this idea, the inventors prepared a sheet containing phosphor particles made of CASN and / or SCASN and a specific resin by the method described in the above <Sheet Preparation Procedure>, and adopted an index related to the transmitted light when the sheet was placed on a blue LED as a design index. Specifically, It / Ii was set as an index corresponding to the degree of absorption of blue light by the sheet, and Ip / Ii was set as an index corresponding to the degree of conversion efficiency from blue light to red light by the sheet. The inventors have found that phosphor particles having It / Ii of 0.2 or less and Ip / Ii of 0.05 or more are preferably used for the wavelength conversion member of a projector. Using such phosphor particles to form the wavelength conversion member of a projector leads to a wider color gamut of the projector.
[0026] Incidentally, if the silicone resin OE-6630 manufactured by Dow Corning Toray is not available for sheet production, the silicone materials for LEDs SCR-1011, SCR-1016, or KER-6100 / CAT-PH manufactured by Shin-Etsu Chemical Co., Ltd. can be used as a substitute (usage amount is the same as OE-6630). According to the knowledge of the present inventors, even if these materials manufactured by Shin-Etsu Chemical Co., Ltd. are used instead of OE-6630, the values of It / Ii and Ip / Ii are almost unchanged.
[0027] In obtaining the phosphor particles of this embodiment, it is important to select not only an appropriate material but also an appropriate manufacturing method and manufacturing conditions. By appropriately selecting the manufacturing method and manufacturing conditions, the particle size and particle shape can be appropriately controlled, and phosphor particles having an It / Ii of 0.2 or less and an Ip / Ii of 0.05 or more can be easily obtained. Details of the manufacturing conditions will be described later, but for example, by appropriately selecting conditions for the low-temperature firing process (annealing process), acid treatment process, and grinding process described below, phosphor particles having an It / Ii of 0.2 or less and an Ip / Ii of 0.05 or more can be obtained.
[0028] It is sufficient that It / Ii is 0.2 or less, preferably 0.15 or less, and more preferably 0.1 or less. The lower limit of It / Ii may be zero. Ip / Ii may be 0.05 or more, preferably 0.07 or more, and more preferably 0.1 or more. The upper limit of Ip / Ii is, for example, 0.5 from the viewpoint of practical design.
[0029] Incidentally, the wavelength conversion element manufactured using the phosphor particles of this embodiment tends to generate relatively little heat when irradiated with blue light. This is thought to be because the phosphor particles of this embodiment are designed with the "transmission" of light in mind, and are easy to form into a thin phosphor layer (composite) (if the phosphor layer is thin, it is thought that heat generation is suppressed accordingly).
[0030] The phosphor particles of this embodiment will be further described below.
[0031] (General formula / composition of CASN and SCASN) The phosphor particles of this embodiment are made of CASN and / or SCASN. Generally, CASN refers to a phosphor whose main crystal phase has the same crystal structure as CaAlSiN3 and whose general formula is MAlSiN3:Eu (M is one or more elements selected from Sr, Mg, Ca, and Ba). In particular, Sr-containing phosphor whose main crystal phase has the same crystal structure as CaAlSiN3 and whose general formula is (Sr,Ca)AlSiN3:Eu is called SCASN. CASN or SCASN refers mainly to the Ca in CaAlSiN3. 2+ A part of Eu acts as a luminescence center. 2+ By being substituted with, it acts as a red-emitting phosphor. Whether the main crystal phase of the produced CASN or SCASN has the same crystal structure as CaAlSiN3 crystals can be confirmed by powder X-ray diffraction. The phosphor particles of this embodiment do not exclude CASN / SCASN containing unavoidable elements and impurities. However, from the viewpoint of good light emission characteristics and improved visibility of the display, the fewer the unavoidable elements and impurities, the better.
[0032] The oxygen content of the phosphor particles of this embodiment is preferably 1% by mass or more, and more preferably from 1% by mass to 5% by mass. CASN / SCASN phosphors may react with moisture and deteriorate. To prevent deterioration, it is preferable to form an oxide film on the particle surface. As a result of the oxide film formation, the oxygen content can become the above-mentioned value. Incidentally, as the particle diameter becomes smaller, the specific surface area increases, so the area of the oxide film on the particle surface increases and the amount of oxygen tends to increase. Incidentally, the oxide film is usually formed in the acid treatment process described below.
[0033] (particle size) The volume-based cumulative 50% diameter and the volume-based cumulative 90% diameter of the phosphor particles of this embodiment measured by a laser diffraction scattering method are respectively represented as D 50 and D. 90 Then, D 50 is, for example, 10 μm or less, preferably 5 μm or less, more preferably 0.2 μm or more and 5 μm or less, and further preferably 0.5 μm or more and 3 μm or less. 90 is, for example, 17 μm or less, preferably 10 μm or less, more preferably 8 μm or less, and further preferably 5 μm or less. The lower limit of D90 is, for example, 2 μm, specifically 3 μm, and more specifically 5 μm. D 50 and D. 90 is a value measured by placing 0.5 g of phosphor particles in 100 mL of ion-exchanged aqueous solution containing 0.05 mass % sodium hexametaphosphate, and dispersing the solution for 3 minutes using an ultrasonic homogenizer with an oscillation frequency of 19.5 ± 1 kHz and an amplitude of 31 ± 5 μm, with the tip placed in the center of the solution.
[0034] (Various characteristics) The phosphor particles of this embodiment preferably have an optical absorptance of 20% or less for light with a wavelength of 700 nm, more preferably 15% or less, and even more preferably 10% or less. The lower limit of the optical absorptance for light with a wavelength of 700 nm is practically 1%. Light with a wavelength of 700 nm is not inherently absorbed by Eu, an activator element of the phosphor. By evaluating the degree of absorption of light with a wavelength of 700 nm, it is possible to confirm the degree of absorption of excess light due to defects in the phosphor. By producing phosphor particles with a small light absorption rate for light with a wavelength of 700 nm, it is possible to obtain phosphor particles suitable for use in wavelength conversion members of projectors.
[0035] The phosphor particles of this embodiment preferably have a 455 nm light absorptance of 75% or more and 99% or less, more preferably 80% or more and 96% or less. Designing the 455 nm light absorptance within this range prevents unnecessary transmission of light from blue LEDs, making it suitable for use as a wavelength conversion member for projectors.
[0036] The phosphor particles of this embodiment preferably have an internal quantum efficiency of 50% or more, more preferably 60% or more, and even more preferably 65% or more. With an internal quantum efficiency of 50% or more, the light from the blue LED is absorbed appropriately and sufficient red light is emitted. There is no upper limit to the internal quantum efficiency, but it is, for example, 90%.
[0037] The phosphor particles of this embodiment preferably have an external quantum efficiency of 35% or more, more preferably 50% or more, and even more preferably 60% or more. With an external quantum efficiency of 35% or more, the light from the blue LED is absorbed appropriately and sufficient red light is emitted. There is no particular upper limit to the external quantum efficiency, but it is, for example, 86% or less.
[0038] (Method of manufacturing phosphor particles) The method for producing the phosphor particles of this embodiment is not particularly limited. The phosphor particles can be produced by selecting an appropriate material, as well as an appropriate production method and production conditions.
[0039] A mixing process in which the starting materials are mixed to form a raw material mixture powder; A firing process for firing the raw material mixed powder obtained in the mixing process to obtain a fired product; A low-temperature firing process (annealing process) is carried out after the fired product obtained in the firing process is powdered. A grinding process for grinding the low-temperature fired powder obtained after the low-temperature firing process into fine powder; A decantation process to remove the fine powder generated during the grinding process. - Acid treatment process to remove impurities thought to be derived from the firing process.
[0040] Incidentally, in this embodiment, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.
[0041] The inventors have found that, in particular, (i) performing the grinding step under appropriate conditions using a ball mill, (ii) performing the decantation step appropriately, and (iii) performing the acid treatment step appropriately, it is easy to produce phosphor particles having an It / Ii of 0.4 or less and an Ip / Ii of 0.03 or more. This production method is different from the conventional CASN / SCASN production method. However, the phosphor particles of this embodiment can adopt various other specific production conditions, provided that the above-mentioned production method ingenuity is adopted.
[0042] Each of the above steps will now be described.
[0043] ·Mixing process In the mixing step, the starting materials are mixed to form a raw material mixed powder. Examples of the starting material include europium compounds, strontium compounds such as strontium nitride, calcium compounds such as calcium nitride, silicon nitrides such as α-type silicon nitride, and aluminum nitride. The above starting materials are preferably in the form of powder.
[0044] Examples of europium compounds include oxides containing europium, hydroxides containing europium, nitrides containing europium, oxynitrides containing europium, and halides containing europium. These can be used alone or in combination of two or more. Among these, it is preferable to use europium oxide, europium nitride, and europium fluoride alone, and it is more preferable to use europium oxide alone.
[0045] In the firing process, europium is divided into those that form a solid solution, those that volatilize, and those that remain as heterogeneous phase components. The heterogeneous phase components that contain europium can be removed by acid treatment or the like. However, if too much is produced, insoluble components are produced by acid treatment, and the brightness decreases. Also, as long as the heterogeneous phase does not absorb excess light, it is acceptable for it to remain, and europium may be contained in this heterogeneous phase.
[0046] The total amount of europium used is not particularly limited, but is preferably at least three times, and more preferably at least four times, the amount of europium that is dissolved in the final phosphor particles. Although the total amount of europium used is not particularly limited, it is preferably 18 times or less the amount of europium dissolved in the final phosphor particles, which can reduce the amount of insoluble heterogeneous phase components generated by the acid treatment and further improve the brightness of the resulting phosphor particles.
[0047] In the mixing step, the raw material mixed powder can be obtained, for example, by a method of dry mixing the starting materials, or a method of wet mixing in an inert solvent that does not substantially react with each starting material, followed by removing the solvent. As a mixing device, for example, a small mill mixer, a V-type mixer, a rocking mixer, a ball mill, a vibration mill, etc. can be used. After mixing using the device, the raw material mixed powder can be obtained by removing aggregates using a sieve as necessary. In order to prevent deterioration of the starting materials and unintended inclusion of oxygen, the mixing step is preferably carried out in a nitrogen atmosphere and in an environment with as little moisture (humidity) as possible.
[0048] · Firing process In the firing step, the raw material powder mixture obtained in the mixing step is fired to obtain a fired product. The firing temperature in the firing step is not particularly limited, but is preferably 1800°C or higher and 2100°C or lower, and more preferably 1900°C or higher and 2000°C or lower. By setting the firing temperature to the above lower limit or higher, the grain growth of the phosphor particles proceeds more effectively, thereby making it possible to further improve the light absorptance, internal quantum efficiency, and external quantum efficiency. By setting the firing temperature to the above upper limit or less, decomposition of the phosphor particles can be further suppressed, and therefore the light absorptance, internal quantum efficiency, and external quantum efficiency can be further improved. Other conditions in the firing step, such as the temperature rise time, temperature rise rate, heating retention time, and pressure, are not particularly limited and may be appropriately adjusted depending on the raw materials used. Typically, the heating retention time is preferably 3 to 30 hours, and the pressure is preferably 0.6 to 10 MPa. From the viewpoint of controlling the oxygen concentration, the firing step is preferably carried out in a nitrogen gas atmosphere. That is, the firing step is preferably carried out in a nitrogen gas atmosphere at a pressure of 0.6 to 10 MPa.
[0049] In the firing step, the method of firing the mixture can be, for example, a method in which the mixture is filled into a container made of a material (such as tungsten) that does not react with the mixture during firing and heated in a nitrogen atmosphere.
[0050] The fired product obtained through the firing step is usually a granular or lumpy sintered body. The fired product can be powdered once by using a process such as crushing, grinding, or classification, either alone or in combination. A specific processing method includes, for example, pulverizing the sintered body to a predetermined particle size using a general pulverizer such as a ball mill, a vibration mill, a jet mill, etc. However, care should be taken because excessive pulverization may produce fine particles that easily scatter light or may cause crystal defects on the particle surface, resulting in a decrease in luminous efficiency.
[0051] Low-temperature firing process (annealing process) After the firing step, a low-temperature firing step (annealing step) may be further included in which the fired product (preferably once powdered) is heated at a temperature lower than the firing temperature in the firing step to obtain a low-temperature fired powder. The low-temperature firing step (annealing step) is preferably carried out in a non-oxidizing atmosphere other than pure nitrogen, such as an inert gas such as a rare gas or nitrogen gas, a reducing gas such as hydrogen gas, carbon monoxide gas, hydrocarbon gas, or ammonia gas, or a mixture of these gases, or in a vacuum, etc. It is particularly preferably carried out in a hydrogen gas atmosphere or an argon atmosphere. The low-temperature firing step (annealing step) may be performed under atmospheric pressure or under pressure. The heat treatment temperature in the low-temperature firing step (annealing step) is not particularly limited, but is preferably 1200 to 1700° C., and more preferably 1300 to 1600° C. The time for the low-temperature firing step (annealing step) is not particularly limited, but is preferably 3 to 12 hours, and more preferably 5 to 10 hours. By performing a low-temperature firing process (annealing process), the luminous efficiency of the phosphor particles can be sufficiently improved. In addition, the rearrangement of elements removes distortions and defects, so the transparency can also be improved. These are favorable in terms of adjusting It / Ii and Ip / Ii. In the low-temperature firing process (annealing process), heterogeneous phases may occur, but these can be sufficiently removed by the process described below.
[0052] Crushing process In the pulverization step, the powder obtained in the low-temperature firing step (annealing step) is pulverized into fine powder. In particular, the powder after the acid treatment step is preferably subjected to the pulverization step using a ball mill. By pulverizing the powder at a rotation speed that is neither too fast nor too slow, and for a time that is neither too long nor too short, phosphor particles having an It / Ii of 0.2 or less and an Ip / Ii of 0.05 or more can be easily obtained. In particular, it is preferable that the grinding by the ball mill is performed in a wet manner using ion-exchanged water and zirconia balls. Although the details are unclear, it is presumed that the surface properties of the powder to be processed are appropriately adjusted / modified by using water and zirconia balls.
[0053] Decantation process In the decantation process, the phosphor particles that have been pulverized through the pulverization process are put into a suitable dispersion medium to precipitate the phosphor particles. The supernatant liquid is then removed. This makes it possible to remove fine particles (ultrafine powder) that may adversely affect optical properties. This makes it easy to obtain phosphor particles with an It / Ii ratio of 0.2 or less and an Ip / Ii ratio of 0.05 or more. As the dispersion medium, for example, an aqueous solution of sodium hexametaphosphate can be used. The decantation operation may be carried out repeatedly. After the decantation process is completed, the resulting precipitate is filtered and dried, and if necessary, a sieve is used to remove coarse particles. In this way, phosphor particles with reduced fine particles (ultrafine powder) can be obtained.
[0054] Acid treatment process In the acid treatment process, the phosphor particles obtained in the decantation process, in which fine particles (ultrafine powder) have been reduced, are treated with acid. This makes it possible to remove at least a portion of the impurities that do not contribute to light emission. Incidentally, it is presumed that the impurities that do not contribute to light emission are generated during the firing process or low-temperature firing process (annealing process).
[0055] The acid may be an aqueous solution containing one or more acids selected from hydrofluoric acid, sulfuric acid, phosphoric acid, hydrochloric acid, and nitric acid. In particular, hydrofluoric acid, nitric acid, and a mixed acid of hydrofluoric acid and nitric acid are preferred. The acid treatment can be carried out by dispersing the low-temperature calcined powder in an aqueous solution containing the above-mentioned acid. The stirring time is, for example, from 10 minutes to 6 hours, preferably from 30 minutes to 3 hours. The stirring temperature can be, for example, from 40°C to 90°C, preferably from 50°C to 70°C. After the acid treatment step, it is preferable to separate substances other than the phosphor particles by filtration and to wash the substances adhering to the phosphor particles with water.
[0056] Through the series of steps described above, the phosphor particles of this embodiment can be obtained.
[0057] <Composite, wavelength conversion member, and projector> Fig. 1 is a schematic diagram showing an example of a wavelength conversion member, which is a so-called transmission type rotating fluorescent plate.
[0058] In the wavelength conversion member, a phosphor layer 2 is formed along the rotation direction of a disk-shaped substrate 1 that is rotated by a motor 3. The region where the phosphor layer 2 is formed includes a blue light incident region where blue light (typically blue laser light) from a blue light source is incident. When the substrate 1 is rotated around the rotation axis by the motor 3, the blue light incident region moves relatively to the substrate 31 around the rotation axis.
[0059] The phosphor layer 2 is a composite material including phosphor particles and a sealant that seals the phosphor particles. Examples of the sealing material for forming the phosphor layer 2 (composite) include silicone resin materials. Regarding silicone resin materials, those that are cured by heat and / or light are supplied by Toray Dow Corning Co., Ltd., Shin-Etsu Chemical Co., Ltd., and the like. Silicone resins are preferable from the viewpoints of transparency as well as heat resistance. Examples of preferable sealing materials include the above-mentioned silicone resin OE-6630 manufactured by Toray Dow Corning Co., Ltd., and LED silicone materials SCR-1011, SCR-1016, and KER-6100 / CAT-PH manufactured by Shin-Etsu Chemical Co., Ltd. In addition, examples of sealing materials include epoxy resin materials and urethane resin materials. The amount of phosphor particles in the phosphor layer 2 (composite) is, for example, 10 to 70% by mass, and preferably 25 to 55% by mass.
[0060] The substrate 1 is preferably made of a material that transmits visible light. Examples of materials for the substrate 1 include quartz glass, crystal, sapphire, optical glass, and transparent resin. A dielectric multilayer film (not shown) may be provided between the substrate 1 and the phosphor layer 2. The dielectric multilayer film functions as a dichroic mirror, transmitting blue light with a wavelength of about 450 nm and reflecting light of 490 nm or more, which includes the wavelength range of the fluorescence emitted from the phosphor layer 2 (490 nm to 750 nm). The shape of the substrate 1 is typically a disk shape, but is not limited to a disk shape.
[0061] The phosphor layer 2 rotates together with the substrate 1 during use. In such a substrate 1, when blue light (laser light) is incident on the phosphor layer 2, a portion of the phosphor layer 2 corresponding to the blue light incident region generates heat. Then, as the substrate 1 rotates, this heated portion (heat generating portion) moves in a circle around the axis of rotation, and then returns to the blue light incident region again, repeating this cycle. In this way, by successively changing the irradiation position of the blue light on the phosphor layer 2, excessive heat generation is suppressed.
[0062] At least a part of the blue light incident on the wavelength conversion member is wavelength-converted to red light by the phosphor layer 2 containing CASN and / or SCASN. At least a part of the red light is emitted to the side opposite to the side where the blue light is incident.
[0063] A projector that uses a blue light source typically includes a blue light source such as a blue laser, a wavelength conversion member that converts the wavelength of the blue light emitted from the blue light source, a modulation element that modulates the light emitted from the wavelength conversion element using an image signal, and our optical system that projects the light modulated by the modulation element. For specific configurations of the wavelength conversion element and the projector, reference can be made to, for example, Fig. 1 and its description in Patent Document 1, the description in JP-A-2013-92796, etc. In addition, known techniques can be appropriately applied to configure the wavelength conversion element and the projector.
[0064] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. Incidentally, in this specification, the wavelength conversion element is described as being of the so-called "transmission type", but even if the wavelength conversion element is of the so-called "reflective type", the phosphor particles of this embodiment are preferably used for manufacturing the wavelength conversion element. Even if the wavelength conversion element is of the reflective type, if the phosphor layer is thin, some of the blue light passes through the phosphor layer without being absorbed, the excitation light is reflected by the reflective surface on the back side of the phosphor layer, and some of the excitation light is absorbed by the phosphor layer again and comes out, so the reflective type and the transmission type have the same concept. EXAMPLES
[0065] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. It should be noted that the present invention is not limited to the Examples.
[0066] Example 1 The phosphor particles made of SCASN in Example 1 are A mixing process in which the starting materials are mixed to form a raw material mixture powder; A firing process for firing the raw material mixed powder obtained in the mixing process to obtain a fired product; A low-temperature firing process (annealing process) is carried out after the fired product obtained in the firing process is powdered. A grinding process for grinding the low-temperature fired powder obtained after the low-temperature firing process into fine powder; A decantation process to remove the fine powder generated during the grinding process. - Acid treatment process to remove impurities thought to be derived from the firing process It was manufactured through each of the above steps. These steps will be described in detail below.
[0067] ·Mixing process The following were mixed in a glove box maintained in a nitrogen atmosphere with a moisture content of 1 ppm by mass or less and an oxygen content of 1 ppm by mass or less. α-type silicon nitride powder (Si3N4, SN-E10 grade, manufactured by Ube Industries) 25.65% by mass Calcium nitride powder (Ca3N2, manufactured by Taiheiyo Cement Corporation) 2.98% by mass Aluminum nitride powder (AlN, E grade, Tokuyama Corporation) 22.49% by mass Strontium nitride powder (Sr2N, Materion) 43.09% by mass Europium oxide powder (Eu2O3, manufactured by Nippon Yttrium Co., Ltd.) 5.79% by mass
[0068] Incidentally, the nitrogen content is determined when the raw materials are mixed according to the above molar ratio.
[0069] To achieve sufficient dispersion and mixing, mixing was carried out using a small mill mixer. After the mixing was completed, the mixture was passed through a sieve with 150 μm openings to remove aggregates, and this was used as a raw material mixed powder.The raw material mixed powder was then filled into a tungsten container with a lid.
[0070] · Firing process The container filled with the raw material powder mixture was taken out of the glove box and quickly placed in an electric furnace equipped with a carbon heater, and the inside of the furnace was thoroughly evacuated to a vacuum of 0.1 Pa or less. Heating was started while continuing the vacuum evacuation, and after the temperature reached 850°C, nitrogen gas was introduced into the furnace to keep the atmospheric pressure in the furnace constant at 0.8 MPaG. After the introduction of nitrogen gas was started, the temperature was continued to rise to 1950°C. The firing was continued for 4 hours at the holding temperature (1950°C), after which the heating was stopped and the material was cooled. After cooling to room temperature, the red lumps collected from the container were crushed in a mortar. Finally, the powder (fired material) was obtained by passing the sieve with 250 μm openings.
[0071] Low-temperature firing process (annealing process) The sintered product obtained in the sintering process was packed into a cylindrical boron nitride container and then placed in an electric furnace equipped with a carbon heater, and then held at 1350°C for 8 hours in an argon flow atmosphere at atmospheric pressure to obtain a low-temperature sintered powder.
[0072] Crushing process The low-temperature fired powder obtained in the low-temperature firing step was put into a mixture of water and ethanol to prepare a dispersion. This dispersion was then ball milled using a ball mill (zirconia balls). The ball milling time and rotation speed were as shown in Table 1. As a result, a pulverized powder was obtained.
[0073] Decantation process In order to remove ultrafine powder from the pulverized powder after the pulverization step, a decantation step was carried out to remove fine powder from the supernatant liquid in which the pulverized powder was settling after the pulverization step. Incidentally, the decantation operation was carried out by calculating the settling time of the phosphor particles using the Stokes' law, with the setting to remove particles with a diameter of 2 μm or less, and at the same time as the settling time reached a settling time, the supernatant liquid above a settling height was removed. An aqueous solution of ion-exchanged water containing 0.05% by mass of sodium hexametaphosphate was used as the dispersion medium, and a device was used that could remove the supernatant liquid by sucking up the liquid above through a tube with an intake port installed at a settling height in a cylindrical container. The decantation operation was carried out repeatedly.
[0074] ·Filtration / drying process The precipitate obtained in the decantation step was filtered, dried, and passed through a sieve with 75 μm openings to remove coarse particles that did not pass through the sieve.
[0075] Acid treatment process In order to remove impurities that were likely produced during firing, an acid treatment was carried out. Specifically, the powder that passed through the sieve was immersed in 0.5 M hydrochloric acid so that the powder concentration was 26.7% by mass, and was further subjected to an acid treatment in which the powder was stirred for 1 hour while being heated. Thereafter, the powder and the hydrochloric acid solution were separated by filtration at a room temperature of about 25°C, and the powder was washed with pure water. After that, the powder washed with pure water was dried for 12 hours in a dryer at 100°C to 120°C. The dried powder was then classified using a sieve with an opening of 75 μm. In this manner, phosphor particles of Example 1 were obtained.
[0076] Comparative Example 1 The phosphor particles of Comparative Example 1 were obtained in the same manner as in Example 1, except that the decantation process was not performed (i.e., the phosphor particles were obtained by filtering and drying the particles "whole" dispersed in an aqueous solution of sodium hexametaphosphate).
[0077] Comparative Example 2 A phosphor of Comparative Example 2 was obtained in the same manner as in Example 1, except that the acid treatment step was not carried out.
[0078] Comparative Example 3 A phosphor of Comparative Example 3 was obtained in the same manner as in Example 1, except that the grinding step and the acid treatment step were not carried out.
[0079] (Examples 2 and 3, and Comparative Examples 4 and 5) The phosphors of Examples 2 and 3 and Comparative Examples 4 and 5 were produced by changing the grinding time in the grinding step in Example 1, as shown in Table 1. 50 and / or D. 90 In order to change the amount of the powder, the grinding time in the grinding step was set to 20 hours, 5 hours, 4 hours, and 1 hour, respectively. The steps other than the grinding time in the grinding step were the same as those in Example 1.
[0080] Example 4 Phosphor particles of Example 4 were obtained in the same manner as in Example 1, except that the firing time in the firing step (time for holding at 1950° C.) was changed to 8 hours and the pulverization time was changed to 15 hours.
[0081] Comparative Example 6 Phosphor particles were obtained in the same manner as in Example 4, except that the pulverization step was not carried out.
[0082] <Confirmation of crystal structure> The crystal structure of each of the phosphor particles in the examples and comparative examples was confirmed by a powder X-ray diffraction pattern using Cu-Kα radiation using an X-ray diffractometer (Ultima IV manufactured by Rigaku Corporation). The powder X-ray diffraction patterns of the phosphor particles of the examples and comparative examples were identical to those of the (Sr, Ca)AlSiN3 crystal. In other words, it was confirmed that the SCASN phosphors obtained in the examples and comparative examples had the same crystal structure as the (Sr, Ca)AlSiN3 main crystal phase.
[0083] The sheets of each phosphor and the evaluation of the optical properties were performed according to the following procedure.
[0084] <Sheet manufacturing procedure> (1) 40 parts by mass of phosphor particles and 60 parts by mass of silicone resin OE-6630 manufactured by Dow Corning Toray Co., Ltd. were mixed and degassed using a rotation / revolution mixer to obtain a uniform mixture. The rotation / revolution mixer used was a Thinky Corporation model ARE-310. Specifically, the mixture was mixed at a rotation speed of 2000 rpm for 2 minutes and 30 seconds, and then degassed at a rotation speed of 2200 rpm for 2 minutes and 30 seconds. (2) The mixture obtained in (1) above was dropped onto a transparent fluororesin film (NR5100-003:100P, manufactured by Fluorochemical Co., Ltd.), and another transparent fluororesin film was placed on top of the dropped mixture. This was formed into an uncured sheet using a roller with a gap of twice the thickness of the film plus 50 μm. (3) The uncured sheet obtained in (2) above was heated at 150° C. for 60 minutes, and then the fluororesin film was peeled off to obtain a cured sheet having a thickness of 50±5 μm.
[0085] <Optical properties> Using the device shown in Figure 2, blue light emitted from a blue LED with a peak wavelength in the range of 450nm to 460nm was irradiated onto one side of the cured sheet (the intensity of this blue light at the peak wavelength is Ii [W / nm]). Then, the intensity It [W / nm] of the peak wavelength in the range of 450nm to 460nm and the intensity Ip [W / nm] of the peak wavelength in the range of 600nm to 650nm of the light emitted from the other side of the cured sheet were measured. Then, It / Ii and Ip / Ii were calculated.
[0086] In the above measurements, the following blue LED was used. Part number: SMT type PLCC-6 0.2W SMD 5050 LED Peak wavelength: 450nm-460nm Chromaticity x:0.145-0.165 Chromaticity y:0.023-0.037
[0087] In addition, in FIG. 2, the distance between the upper surface of the blue LED and the lower surface of the cured sheet was 2 mm.
[0088] <D 50 and D. 90 Measurements > D of each phosphor particle in the examples and comparative examples 50 and D. 90 was measured using a particle size measuring device using the laser diffraction and scattering method, Microtrac MT3300EXII (Microtrac Bell Co., Ltd.). The specific measurement procedure is as follows.
[0089] (1) 0.5 g of phosphor was added to 100 mL of an aqueous solution of ion-exchanged water mixed with 0.05% by mass of sodium hexametaphosphate, and the homogenizer was ultrasonically homogenized for 3 minutes using an Ultrasonic Homogenizer US-150E (Nihon Seiki Seisakusho Co., Ltd., Amplitude 100%, oscillation frequency 19.5±1 kHz, tip size 20 mmφ, amplitude approximately 31 μm) by placing the tip in the center of the liquid. This resulted in a dispersion liquid for measurement. (2) After that, the particle size distribution of the phosphor particles in the dispersion liquid for measurement was measured using the particle size measuring device. From the obtained particle size distribution, D 50 and D. 90 asked for.
[0090] <Oxygen content measurement> The oxygen content of each phosphor particle in the examples and comparative examples was measured using an oxygen and nitrogen analyzer (EMGA-920, manufactured by Horiba, Ltd.) The oxygen content was determined by (i) placing the phosphor particles in a graphite crucible, removing surface adsorbates at 280°C, and then heating to 2400°C, and subtracting from the measured oxygen content (ii) the background oxygen content obtained by treating the particles under the same conditions in an empty graphite crucible.
[0091] <Measurement of 700nm light absorption rate> The 700 nm light absorptance of each of the phosphor particles in the examples and comparative examples was measured by the following procedure. A standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was set at the opening of the integrating sphere, and monochromatic light separated into a wavelength of 700 nm from a light emitting source (Xe lamp) was introduced into the integrating sphere through an optical fiber, and the reflected light spectrum was measured with a spectrophotometer (MCPD-7000 manufactured by Otsuka Electronics Co., Ltd.). At that time, the number of incident light photons (Qex(700)) was calculated from the spectrum in the wavelength range of 690 to 710 nm. Next, the concave cell was filled with phosphor particles so that the surface was smooth, and then it was set in the opening of the integrating sphere. Monochromatic light with a wavelength of 700 nm was irradiated, and the incident reflected light spectrum was measured with a spectrophotometer. The incident reflected light photon count (Qref(700)) was calculated from the obtained spectrum data. The incident reflected light photon count (Qref(700)) was calculated in the same wavelength range as the incident light photon count (Qex(700)). The 700 nm light absorptance was calculated from the obtained two types of photon counts based on the following formula. 700 nm light absorption rate = ((Qex(700)-Qref(700)) / Qex(700) x 100
[0092] <Measurements of 455nm light absorption rate, internal quantum efficiency, external quantum efficiency, and peak wavelength> The 455 nm light absorptance, internal quantum efficiency and external quantum efficiency of each of the phosphor particles in the examples and comparative examples were calculated by the following procedure.
[0093] The phosphor particles were filled in a concave cell so that the surface was smooth, and attached to the opening of an integrating sphere. Monochromatic light, which was split into 455 nm wavelengths from a light emission source (Xe lamp), was introduced into the integrating sphere using an optical fiber as excitation light for the phosphor. This monochromatic light was irradiated onto a phosphor sample, and the fluorescence spectrum of the sample was measured using a spectrophotometer (MCPD-7000 manufactured by Otsuka Electronics Co., Ltd.). From the obtained spectral data, the number of excitation reflected light photons (Qref) and the number of fluorescence photons (Qem) were calculated. The number of excitation reflected light photons was calculated in the same wavelength range as the number of excitation light photons, and the number of fluorescence photons was calculated in the range of 465 to 800 nm.
[0094] In addition, using the same device, a standard reflector with a reflectance of 99% (Spectralon (registered trademark) manufactured by Labsphere) was attached to the opening of the integrating sphere to measure the spectrum of excitation light with a wavelength of 455 nm. At that time, the number of excitation light photons (Qex) was calculated from the spectrum in the wavelength range of 450 to 465 nm. The 455 nm light absorptance and internal quantum efficiency of each phosphor in the examples and comparative examples were calculated by the following formulas. 455 nm light absorption rate = {(Qex-Qref) / Qex} x 100 Internal quantum efficiency = {Qem / (Qex-Qref)} x 100 Incidentally, the external quantum efficiency can be calculated by the following formula. External quantum efficiency = (Qem / Qex) x 100 Therefore, from the above formula, the external quantum efficiency has the following relationship: External quantum efficiency = 455 nm light absorptance × internal quantum efficiency The peak wavelength of the phosphor particles in the examples and comparative examples was determined to be the wavelength that showed the highest intensity in the wavelength range of 465 nm to 800 nm in the spectrum data obtained by attaching the phosphor to the opening of an integrating sphere.
[0095] <Measurement of the x value (chromaticity X) of the cured sheet> The x value (chromaticity X) of the cured sheet using the phosphor particles of the examples and comparative examples was determined by calculating the CIE chromaticity coordinate x value (chromaticity X) in the XYZ color system defined in JIS Z8701 from the wavelength range data of the emission spectrum in the range of 400 nm to 800 nm, in accordance with JIS Z 8724. A larger x value is preferable because it leads to a wider color gamut of the projector (wider red expression range).
[0096] The production conditions (including the raw material composition) and the evaluation results of each of the examples and comparative examples are shown in Table 1.
[0097] [Table 1]
[0098] As shown in Table 1, in the examples where It / Ii was 0.2 or less and Ip / Ii was 0.05 or more, a large x value was obtained. In other words, it was shown that the phosphor particles of the examples are preferably used in terms of widening the color gamut of projectors using blue laser light. On the other hand, in the comparative examples in which It / Ii was greater than 0.2 and / or Ip / Ii was less than 0.05, the x value was smaller than that in the examples. Just to be clear, the x value in Comparative Example 2 is 0.349, and the x value in Example 3 is 0.364. Although this difference may seem small at first glance, when it comes to the issue of widening the color gamut, this difference is significant.
[0099] Incidentally, from the examples and comparative examples shown in Table 1, even when the same raw materials are used, It / Ii and Ip / Ii change depending on the ball mill grinding conditions (time), whether or not decantation is performed, whether or not acid treatment is performed, etc. From this, it can be seen that by selecting appropriate raw materials as well as appropriate manufacturing conditions, phosphor particles with It / Ii of 0.2 or less and Ip / Ii of 0.05 or more can be obtained.
[0100] This application claims priority based on Japanese Patent Application No. 2020-128976, filed on July 30, 2020, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]
[0101] 1 Board 2 Phosphor layer (composite) 3 Motor
Claims
1. A phosphor particle for manufacturing a wavelength conversion member of a projector, the phosphor particle being made of CASN and / or SCASN, A cured sheet produced by the following sheet production procedure satisfies the following optical properties: Phosphor particles having an optical absorptivity of 20% or less for light with a wavelength of 700 nm. <Sheet manufacturing procedure> (1) 40 parts by mass of the phosphor particles and 60 parts by mass of silicone resin OE-6630 manufactured by Dow Corning Toray Co., Ltd. are mixed and degassed using a rotation / revolution mixer to obtain a uniform mixture. (2) The mixture obtained in (1) is dropped onto a transparent first fluororesin film, and a transparent second fluororesin film is further laminated on the dropped mixture to obtain a sheet-like material. This sheet-like material is formed into an uncured sheet using a roller having a gap of 50 μm plus the total thickness of the first fluororesin film and the second fluororesin film. (3) The uncured sheet obtained in (2) above is heated at 150° C. for 60 minutes, after which the first fluororesin film and the second fluororesin film are peeled off to obtain a cured sheet having a thickness of 50±5 μm. <Optical properties> When the intensity at the peak wavelength of blue light emitted from a blue LED having a peak wavelength in the range of 450 nm to 460 nm is Ii [W / nm], and when the blue light is irradiated onto one side of the cured sheet, the intensity of the peak wavelength in the range of 450 nm to 460 nm of the light emitted from the other side of the cured sheet is It [W / nm] and the intensity of the peak wavelength in the range of 600 nm to 650 nm is Ip [W / nm], It / Ii is 0.2 or less and Ip / Ii is 0.05 or more.
2. 2. The phosphor particle according to claim 1 , The volume-based cumulative 50% diameter and the volume-based cumulative 90% diameter measured by the laser diffraction scattering method are respectively D 50 and D. 90 When this is done, D 50 is 10 μm or less, and D 90 is a phosphor particle having a size of 17 μm or less. However, D 50 and D. 90 is a value measured using a liquid obtained by adding 0.5 g of the phosphor particles to 100 mL of an ion-exchange aqueous solution containing 0.05% by mass of sodium hexametaphosphate, dispersing the solution for 3 minutes using an ultrasonic homogenizer with an oscillation frequency of 19.5±1 kHz and an amplitude of 31±5 μm, with the tip placed in the center of the liquid.
3. 3. The phosphor particle according to claim 1, Phosphor particles having an oxygen content of 1% by mass or more.
4. A composite comprising the phosphor particles according to any one of claims 1 to 3 and a sealing material that seals the phosphor particles.
5. A wavelength conversion member comprising the composite according to claim 4.
6. A projector comprising the wavelength conversion member according to claim 5 .
Citation Information
Patent Citations
Nitride fluorescent powder with small particle size and high quantum efficiency, preparation method and application thereof, luminescent device and display device
CN112745835A
Wavelength conversion element, light source device, and projector
JP2013162021A
Method of producing phosphor powder
JP2013170184A
Red phosphor and light-emitting device
JP2020012010A
Phosphor and light emitting device
WO2017122800A1
